Self-select target neighboring base station assisted handover for natural disaster in LTE-A network - Azita Laily Yusof; Ainnur Eiza Azhar; Norsuzila Ya’acob (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper presents Self-Select Target Neighboring Base Station Assisted Handover for Natural Disaster in LTE-A Network. In this study, two parameters have been introduced which are known as received signal strength of user (RSS) and left over power of base station (LoP) in order to maintained good QoS of UE and prolong battery life of base station when there is power outage. A distance fraction coefficient (α) with value 0.2 has been introduced to RSS expression to improve the signal strength by reducing the area that the UE’s covered. Both parameters are used to calculate weighted-average score (WAS) for selection of potential target base station to avoid more users to connect to the affected base station. From the results, sRSS=0.8 gave the highest WAS with value of WAS=0.84 for users from 1 to 100 compares to other value of sRSS. Moreover, by using no natural disaster condition as reference, Condition 1 (wRSS=80%, wLoP=20% ) with the lowest percentage of improvement (3.75%.) will be chosen as handover condition as it near to base station, avoid overloaded users to the affected base station, hence prolong battery life as it only use 20% of battery usage.